Analisis Ketersediaan dan Aksesibilitas Obat Obatan pada Korban Bencana Banjir Aceh Tamiang pada Tahun 2025 - Diana Lestari; Meylissa Meylissa; Nia Hairu Novita (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Aceh Tamiang Regency is an area with a high risk of annual flooding. This emergency condition often triggers a surge in environment-related diseases such as skin diseases, respiratory infections, and diarrhea. The success of managing health crises heavily depends on pharmaceutical logistics management, especially the availability of essential medicines and ease of access for refugees at evacuation points. This study aims to analyze the extent of medicine availability at community health centers and health posts, as well as to evaluate the barriers to medicine accessibility for flood victims in Aceh Tamiang Regency. This study uses a qualitative/quantitative descriptive method (choose one) with a case study approach. Primary data were collected through in-depth interviews with pharmaceutical logistics officers and surveys of flood survivors. Secondary data were obtained from the drug stock reports of the Aceh Tamiang District Health Office. Analysis was conducted on variables such as drug types, stock amounts (Buffer Stock), and distribution channels during the emergency response period. The results of the study indicate that the availability of drugs in the initial disaster phase tends to be (state the prediction, e.g., sufficient/limited). However, accessibility is often hindered by damaged road infrastructure and uneven distribution to remote posts. There is an urgent need to strengthen the logistics early warning system so that the types of medicines available match the disease patterns that emerge after floods. Although medicine stocks are generally available in central pharmacy warehouses, geographical constraints and distribution coordination are the main factors hindering accessibility. It is recommended that local governments map out alternative distribution routes and provide disaster-specific buffer stock of medicines at the sub-district level.